1958
DOI: 10.1099/00221287-18-1-173
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Cell-Wall Composition and Taxonomy of Actinomycetales and Related Groups

Abstract: The cell-wall compositions of 51 strains of Actinomyces, Nocardia, Streptomyces, Micromonospora, Mycobacterium and Propionibacterium have been investigated, together with those of 7 strains of Eumycetes. The cell walls of the actinomycetes were made up of sugars, amino sugars and amino acids (the latter few in number). The general pattern of components was thus identical with that previously found for Gram-positive bacteria. In the fungi, however, the mycelial walls were composed entirely of carbohydrate. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(113 citation statements)
references
References 29 publications
10
103
0
Order By: Relevance
“…samples A and D. Table I . This parallels similar findings for other mycobacteria (see Cummins & Harris, 1958;Cummins, 1962). However, during the present work it was noticed that cell-wall suspensions prepared in a sucrose gradient after disintegration of freshly made suspensions of M. Zepraemurium were stable in saline and gave a titre against M .…”
Section: Serological Tests With Mycobacterium Lepraemurium Cell-wall supporting
confidence: 75%
See 2 more Smart Citations
“…samples A and D. Table I . This parallels similar findings for other mycobacteria (see Cummins & Harris, 1958;Cummins, 1962). However, during the present work it was noticed that cell-wall suspensions prepared in a sucrose gradient after disintegration of freshly made suspensions of M. Zepraemurium were stable in saline and gave a titre against M .…”
Section: Serological Tests With Mycobacterium Lepraemurium Cell-wall supporting
confidence: 75%
“…The principal amino acids found were alanine, glutamic acid and DAP, the latter the DL-isomer (or DL+DD), and the principal sugars identified were arabinose and galactose, with a trace of mannose. This pattern of sugar and amino acid components is that to be expected in a mycobacterium (Cummins & Harris, 1958;Cummins, 1962). The identity of the hesoxamines is not known for certain, since the chromatographic method used did not separate glucosamine and muramic acid, but it may be assumed that both are present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1959;Cummins, 1962a, b ;Cummins & Harris, 1956, 1958Perkins & Cummins, 1964;Barber et al 1965bBarber et al , 1966 …”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of cell wall composition, Cummins and Harris (10) proposed that the actinomycetes are not related to the fungi and should be classified with bacteria proper. They also suggested that Nocardia is more closely related to Mycobacterium than to Streptomyces.…”
Section: Methodsmentioning
confidence: 99%